2001
DOI: 10.1002/1097-0274(200101)39:1<42::aid-ajim4>3.0.co;2-i
|View full text |Cite
|
Sign up to set email alerts
|

Identifying and prioritizing gaming workers' health and safety concerns using mapping for data collection

Abstract: Background This research was prompted by the clinical presentation of workers from a variety of gaming occupations with injuries and illnesses and multiple health and safety concerns. Methods Using participatory action research principles, 51 gaming workers in Ontario and 20 gaming workers in Manitoba were consulted during a series of focus group sessions. Mapping exercises were used to survey the participants about their health concerns, perceived occupational hazards and the impact of working conditions on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
19
1

Year Published

2003
2003
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 35 publications
0
19
1
Order By: Relevance
“…Hing and Breen 2005;Wu and Wong 2008), this study confirms that many casino gaming employees experienced high levels of stress. They reported physical and psychological symptoms of impaired health (Hing and Breen 2005;Keith et al 2001). To enhance employees' health protection, job stressors uncovered in the study could be properly controlled, reduced or even eradicated.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Hing and Breen 2005;Wu and Wong 2008), this study confirms that many casino gaming employees experienced high levels of stress. They reported physical and psychological symptoms of impaired health (Hing and Breen 2005;Keith et al 2001). To enhance employees' health protection, job stressors uncovered in the study could be properly controlled, reduced or even eradicated.…”
Section: Discussionmentioning
confidence: 99%
“…Work shifts had interfered opportunities to meet acquaintances and family members causing social isolation and gambling problems (Hing and Breen 2008b;Keith et al 2001). Many felt lonely.…”
Section: Shift Work Led To Social Isolationmentioning
confidence: 99%
See 1 more Smart Citation
“…A one-way ANVOA test found significant differences between the departments (F=3.311, p=0.001), which was further confirmed with a Scheffé post-hoc test. Keith et al (2001) had found that Slots employees perceived their jobs as particularly stressful, but this study found that the Slots employees exhibited, on average, a basically neutral attitude toward the idea that their jobs were stressful, and employees from two other departments agreed more strongly that their jobs were stressful. In addition to feeling different amounts of job stress, employees in the different departments also exhibited different levels of belief in risk cognitions, as is illustrated in Table 68.…”
Section: Departmentmentioning
confidence: 99%
“…In fact, Keith et al (2001) conducted focus groups with gambling industry employees from Ontario and Manitoba and found that stress was one of the most common health and safety concerns the employees mentioned, and slot machine workers described their work areas as particularly stressful. Also, Dangerfield (2004) investigated job stress in her Alberta study and found that 10.7% of the casino employees she surveyed rated their jobs as -extremely stressful,‖ 61.5% as -somewhat stressful,‖ and 27.9% as -not at all stressful,‖ although these stress levels were actually less than those found in a previous survey on job stress in the general Alberta population.…”
mentioning
confidence: 99%